Encouraging tourism in protected areas: horse-riding in national parks in New South Wales, Australia. (2018) - Dragovich, Deirdre
Horse-riding is being encouraged in NSW by government policies and legislation intended to increase tourism. This initiative is examined within the context of protected area management proposed by Weaver and Lawton (2017): parks for visitors, parks with visitors, and the 'aspirational' symbiosis of parks and visitors. Severe erosion of horse riding trails in a near-metropolitan national park was compared with results from a recent horse riding trial in a wilderness area. Park managements have met state government tourism objectives by seeking to create positive relationships between the need for protection (conservation) and the desire of visitors to pursue active recreational opportunities. But will 'parks with visitors' become 'parks and visitors?'